Carbohydrate Over Nutrition Harmfull to both Obese Pregnant Mice and Fetus - Idris, Irfan; Paharu, Kabah; Satriana, Satriana; Tadjuddin Chalid, Maisuri; Wardihan Sinrang, Andi (Nusantara Medical Science Journal, 2023)
Background : Obesity in pregnancy due to carbohydrate over nutrition is still rarely reported and the incidence of obesity in pregnancy in the developing countries begin to increase. The aims of this study is to observe the detrimental effect of obesity in both mother and developing fetus of mice which fed by high carbohydrate diet. Methods : Female mice were divided to four groups. Group 1 (obese group) were fed with high carbohydrate (HC) diet and group 2 (control group) with standard diet for 12 weeks. All mice will be mated until pregnant and terminated for collecting blood with cardiac puncture every trimester. Another mice (7 mice from obese group and 7 mice from control group) will follow until 3rd trimester than terminated to collecting lipid profile of blood and examined the fetal’s anthrophometric. Lipid and blood glucose were examined by chemichal photometric and glucometer kit, while anthrophometric’s variables measured by weight scale and meter scale. Results : Blood glucose, total cholesterol, HDL and LDL are similar between obesity group and normal weight group every trimester, while only blood TG increased in obesity group particularly in first and second trimester of pregnancy. The detrimental effect also found in the developing fetus of obesity group which have significance higher of bodyweight, body lengths, head circumference, and waist circumference. Conclusions: Obesity in pregnancy due to carbohydrate over nutrition could have detrimental effect to both mother and developing fetus.